PEMANFAATAN DATA SATELIT MODIS UNTUK MENENTUKAN FASE TUMBUH TANAMAN PADI DI KECAMATAN HARAU - Delvi Yanti; Tiara Aulia Putri; M. Agita Tjandra (Rona Teknik Pertanian, 2023)
AbstractObservation of the growth phase of rice plants generally takes a long time and cannot cover a large area. With remote sensing, the speed and accuracy of information in agricultural management is easier. The use of MODIS satellite image data in remote sensing technology plays a role in determining the growth phase of rice plants by utilizing the vegetation index value of rice plants. The aim of the study was to determine the regression equation and the range of NDVI (Normalized Difference Vegetation Index) values to predict the growth phase of rice plants in Harau District, Lima Puluh Kota District. Research in the field was carried out based on work maps obtained from the results of the imaging process in ArcGis. The location used as a sample of field observations is Grid ≥45% which is occupied by rice fields. Regression analysis was carried out to obtain a regression equation between plant age and NDVI values, then a range of values was made based on the rice growing phase. The regression equation used to predict the growth phase of rice plants in Harau District based on the NDVI value is y = -0.0000838932x² + 0.0123160507x + 0.2966130658 where x is the age of the plant (days after planting) and y is the NDVI value. The correlation coefficient (r) of the regression equation is 0.966. The range of NDVI values based on the growth phase for Harau District is the Water Phase 0.4722, the Vegetative Phase (1) 0.4722-0.6945; Vegetative phase (2) 0.6945-0.7412; Generative phase (1) 0.7412-0.6363; Generative phase (2) 0.6363-0.5665; Bera 0.5665-0.4799.Keywords:: growth phase; vegetation index; MODIS; NDVIAbstrakPengamatan fase pertumbuhan tanaman padi pada umumnya membutuhkan waktu yang lama dan tidak bisa menjangkau area yang luas. Dengan penginderaan jauh, maka kecepatan dan ketepatan informasi dalam pengelolaan pertanian lebih mudah. Penggunaan data citra satelit MODIS pada teknologi penginderaan jauh berperan dalam menentukan fase tumbuh tanaman padi dengan memnafaatkan nilai indeks vegetasi dari tanaman padi. Tujuan penelitian adalah menentukan persamaan regresi dan rentang nilai NDVI (Normalized Difference Vegetation Index) untuk memprediksi fase tumbuh tanaman padi di Kecamatan Harau Kabupaten Lima Puluh Kota. Penelitian di lapangan dilakukan berdasarkan peta kerja yang diperoleh dari hasil proses pencitraan pada ArcGis. Lokasi yang dijadikan sampel observasi lapangan adalah Grid ≥45% yang ditempati oleh sawah. Analisis regresi dilakukan untuk mendapatkan persamaan regresi antara umur tanaman dan nilai NDVI, kemudian dibuat rentang nilai berdasarkan fase tumbuh padi. Persamaan regresi yang digunakan untuk memprediksi fase tumbuh tanaman padi di Kecamatan Harau adalah y = -0,0000838932x² + 0,0123160507x + 0,2966130658 dengan x sebagai umur tanaman (hari setelah tanam) dan y sebagai nilai NDVI. Koefisien korelasi (r) dari persamaan regresi adalah 0,966.  Rentang nilai NDVI berdasarkan fase tumbuh untuk Kecamatan Harau adalah Fase Air 0,4722, Fase Vegetatif (1) 0,4722-0,6945; Fase vegetatif (2) 0,6945-0,7412; Fase generatif (1) 0,7412-0,6363; Fase generatif (2) 0,6363-0,5665; Bera 0,5665-0,4799.